MODEL SUPERVISI AKADEMIK BERBASIS NILAI ISLAM DALAM MENINGKATKAN MUTU PEMBELAJARAN: STUDI KASUS DI MA MUHAMMADIYAH GORONTALO - Ovenly utomo silangen; Said Subhan Posangi (Jurnal Suluh Pendidikan, 2026)
This study was motivated by the continued dominance of administrative approaches in madrasah supervision practices, which have not been effective in improving the quality of learning. The study aims to analyze and formulate an Islamic-values-based academic supervision model to improve the quality of learning in madrasahs. The study employed a qualitative approach using a case study design conducted at MA Muhammadiyah in Gorontalo City. The research informants consisted of 12 individuals, including madrasah supervisors, madrasah principals, and teachers, selected through purposive and snowball sampling. Data collection techniques included in-depth interviews (45–60 minutes), six participatory observations, and document analysis. The results revealed three main findings: (1) supervision remains dominated by an administrative approach, (2) collaborative supervision based on Islamic values is beginning to emerge, and (3) follow-up on supervision is weak. Based on these findings, this study developed an Islamic-values-based academic supervision model that is integrative, reflective, and sustainable. The implications of this study emphasize the importance of strengthening values-based supervision policies, enhancing supervisors’ competencies, and integrating supervision with teachers’ professional development. The novelty of this study lies in the development of a supervision model that integrates professional dimensions and Islamic values into madrasah supervision practices.